PENERAPAN PENDEKATAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP - Ai Solihat Yulianti; Asep Ikin Sugandi (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
This study aims to to know the achievement of the ability of the solution of the problems a useful or valuable junior high school students who studying used the the problem of fee-based learning with that uses ordinary learning , with material used in this research is a circle of class VIII  junior high school semester the even . The methodology that was used is quantitative,  who is in the form of experiments in support with the data the result of pretes and postes .Population in this research is junior high school students class viii at west bandung. Were selected from research is 34 of the students of experimentation and 32 of the students of control in the academic year 2017 / 2018 .An instrument that is used is math tests the ability of the solution of the problems . Processing the results of the data were analyzed using application ibm spss statistics version 22. Processing analysis data using test normality followed by test of homogeneity then to test t-hitung on the data pretes.While in data postes test normality then to test the average that is mann-whitney test. Based on analysis of the that has been done , obtained that the achievement of the ability problem solving math junior high school students which adopting the problem based learning better than use learning ordinary.